Brazilian Flora 2020: Leveraging the power of a collaborative scientific network - Gomes da Silva, Janaína (2021)
and fungal diversity of Brazil. Overall, a team of about 980 taxonomists joined efforts in a highly collaborative project that used cy-bertaxonomy to prepare an updated Flora of Brazil, showing the power of scientific collaboration to reach ambitious goals. This paperpresents an overview of the Brazilian Flora 2020 and provides taxonomic and spatial updates on the algae, fungi, and plants found inone of the world’s most biodiverse countries. We further identify collection gaps and summarize future goals that extend beyond 2020.Our results show that Brazil is home to 46,975 native species of algae, fungi, and plants, of which 19,669 are endemic to the country.The data compiled to date suggests that the Atlantic Rainforest might be the most diverse Brazilian domain for all plant groups exceptgymnosperms, which are most diverse in the Amazon. However, scientific knowledge of Brazilian diversity is still unequally distrib-uted, with the Atlantic Rainforest and the Cerrado being the most intensively sampled and studied biomes in the country. In times of“scientific reductionism”, with botanical and mycological sciences suffering pervasive depreciation in recent decades, the first onlineFlora of Brazil 2020 significantly enhanced the quality and quantity of taxonomic data available for algae, fungi, and plants from Brazil.This project also made all the information freely available online,providing a firm foundation for future research and for the management,conservation, and sustainable use of the Brazilian funga and flora.